Identification and classification of Aquilaria (Thymelaeaceae): inferences from a phylogenetic study based on matK sequences - Zhaoqi Xie; Siqing Fan; Junyu Xu; Haijing Xiao; Jiaxin Yang; Min Guo; Chunsong Cheng (PeerJ, 2025)
In the realm of Aquilaria classification and grading, a persistent market uncertainty persists, questioning whether the basis should be geographical distribution or biological origin. In this study, the effectiveness of matK molecular markers, particularly through eight stable polymorphic loci (e.g., +249C for Chinese origin, +435G for Aquilaria sinensis), emerges as a decisive tool for differentiating Aquilaria species. The integration of matK and trnL-trnF not only validates this efficacy but also streamlines the systematic categorization of 34 agarwood products into four biogeographic pedigrees: Chinese (C1: A. sinensis; C2: A. malaccensis), Indonesian (A. cumingiana), and Indochinese (A. rugosa). Molecular clock analyses trace the genus’s divergence to 6.78 million years ago (Ma) (A. hirta), with recent speciation of commercially pivotal species (A. sinensis:  0.9 Ma; A. malaccensis:  1.0 Ma). Notably, the redefined placement of Gyrinops walla (5.75 Ma) within Aquilaria challenges prior taxonomic assumptions, suggesting revised genus boundaries. The Median-Joining network further visualized these haplotypes, showing key evolutionary transitions, particularly from A. crassna to A. rugosa and A. malaccensis. These findings provide robust tools for species differentiation, insights into evolutionary history, and practical guidance for conservation and trade applications within the field of botany.